Question 1 of 5Convert to Polar Form.
Select the Correct Answer Below: Correct! Not Correct!
A
$$r=12 \hspace{.1em}\text{cos}\hspace{.1em}θ - 8 \hspace{.1em}\text{sin}\hspace{.1em}θ$$
B
$$r=6 \hspace{.1em}\text{cos}\hspace{.1em}θ + 8 \hspace{.1em}\text{sin}\hspace{.1em}θ$$
C
$$r=-6 \hspace{.1em}\text{cos}\hspace{.1em}θ - 8 \hspace{.1em}\text{sin}\hspace{.1em}θ$$
D
$$r=-6 \hspace{.1em}\text{cos}\hspace{.1em}θ + 4 \hspace{.1em}\text{sin}\hspace{.1em}θ$$
E
$$r=-2 \hspace{.1em}\text{sin}\hspace{.1em}θ$$
Question 2 of 5Convert to Polar Form.
Select the Correct Answer Below: Correct! Not Correct!
A
$$r=10 \hspace{.1em}\text{cos}\hspace{.1em}θ$$
B
$$r=10 \hspace{.1em}\text{sin}\hspace{.1em}θ$$
C
$$r=7 \hspace{.1em}\text{cos}\hspace{.1em}θ + 3 \hspace{.1em}\text{sin}\hspace{.1em}θ$$
D
$$r=14 \hspace{.1em}\text{cos}\hspace{.1em}θ + 6 \hspace{.1em}\text{sin}\hspace{.1em}θ$$
E
$$r=-14 \hspace{.1em}\text{cos}\hspace{.1em}θ - 6 \hspace{.1em}\text{sin}\hspace{.1em}θ$$
Question 3 of 5Convert to Rectangular Form.
Select the Correct Answer Below: Correct! Not Correct!
A
$$\left(x - \frac{1}{2}\right)^{2}+ \left(y + \frac{\sqrt{3}}{2}\right)^{2}=1$$
B
$$\left(x - \frac{\sqrt{3}}{2}\right)^{2}+ \left(y + \frac{1}{2}\right)^{2}=1$$
C
$$\left(x - \sqrt{3}\right)^{2}+ \left(y + 1\right)^{2}=4$$
D
$$\left(x + \sqrt{3}\right)^{2}+ \left(y - 1\right)^{2}=2$$
E
$$\left(x - \frac{1}{2}\right)^{2}+ \left(y - 2\right)^{2}=\frac{3}{2}$$
Question 4 of 5Convert to Rectangular Form.
Select the Correct Answer Below: Correct! Not Correct!
A
$$\left(x - \frac{\sqrt{3}}{2}\right)^{2}+ \left(y - \frac{1}{2}\right)^{2}=1$$
B
$$\left(x - \sqrt{3}\right)^{2}+ \left(y + 1\right)^{2}=4$$
C
$$\left(x - \sqrt{3}\right)^{2}+ \left(y - 1\right)^{2}=4$$
D
$$\left(x - \frac{3}{2}\right)^{2}+ \left(y - \frac{3\sqrt{3}}{2}\right)^{2}=9$$
E
$$\left(x + \frac{1}{2}\right)^{2}+ \left(y + \frac{3\sqrt{3}}{2}\right)^{2}=9$$
Question 5 of 5Convert to Rectangular Form.
Select the Correct Answer Below: Correct! Not Correct!
A
$$\left(x - \frac{\sqrt{3}}{2}\right)^{2}+ \left(y + \frac{1}{2}\right)^{2}=1$$
B
$$\left(x - \sqrt{3}\right)^{2}+ \left(y + 1\right)^{2}=4$$
C
$$\left(x - \frac{\sqrt{2}}{2}\right)^{2}+ \left(y + \frac{\sqrt{2}}{2}\right)^{2}=1$$
D
$$\left(x - \frac{3}{2}\right)^{2}+ \left(y - \frac{3\sqrt{3}}{2}\right)^{2}=9$$
E
$$\left(x - \frac{3\sqrt{3}}{2}\right)^{2}+ \left(y - \sqrt{3}\right)^{2}=9$$

Great Job! You Passed!

Better Luck Next Time...

Restart Quiz ↻
Review Lesson ↻
Next Lesson »